A Successful (Yet Somewhat Untested) Case of Disaster Financing: Terrorism Insurance Under TRIA, 2002–2020. Issue 1 (25th March 2018) - Michel‐Kerjan, Erwann; Kunreuther, Howard
Abstract: The Terrorism Risk Insurance Act (TRIA) established a public–private partnership between the U.S. federal government, private insurers, and all commercial enterprises operating on U.S. soil. Renewed and modified in January 2015 until December 2020, the TRIA program requires insurers to offer terrorism insurance to their commercial policyholders while providing insurers with free up‐front financial protection up to $100 billion against terrorist attacks in the United States. With the federal government providing a financial safety net, the private insurance sector can offer coverage against an uncertain risk that would otherwise be largely considered uninsurable, thus making terrorism insurance widely available and affordable. TRIA is a successful case of public–private disaster risk financing that has received bipartisan political support. Yet it remains untested for large losses and it is unclear how the market and policymakers will react should another large‐scale insured loss occur. TRIA also raises concerns about the indemnification of individual victims of a terrorist attack (in addition to workers' compensation).